Analysis of Consumer Behaviour in Making Decisions after the Covid-19 pandemic: Perspectives on the Theory of Stimulus Organism Response (SOR) - Purwanto, Nuri; Pancaningrum, Erminati; Juwita, Kristin (KnE Social Sciences, 2022)
The COVID-19 pandemic in Indonesia has had an impact on the economy, including changes in consumer behaviour. This study aimed to analyze the effects of advertising and digital marketing strategies on consumer repurchase behaviour. The sample of this study included 150 respondents, selected through the purposive sampling technique. Data collection was done by distributing questionnaires through Google forms to three regions: Jombang, Malang and Surabaya. The questionnaire results were analyzed using the structural equation model (SEM) method. Of the six hypotheses offered, only ‘advertising creativity’ had a significant effect on customer engagement and repurchase behaviour. Customer engagement in and of itself did not affect the relationship either directly to repurchase behaviour or as a variable that mediates the relationship between digital marketing strategies and repurchase behaviour. Digital marketing strategies had no effect on repurchase behaviour. Keywords: Costumer engagement; Digital Content Marketing; Repurchase Buying; Creativity Advertising